Analysis Mathematical Resilience Relationship With Mathematical Problem Solving Ability in Functions Derivative Material : (A case study at the Eleventh Grade of SMAN 1 Klari in teh Academic Year 2022/2023) - Nurhayati (Universitas Subang, 2024)
This study is a correlational research aimed at exploring the relationship between mathematical resilience and problem-solving skills in mathematics. Conducted at a senior high school in Karawang, the research involved a sample of 36 students. The method employed was ex post facto, with purposive sampling to select participants based on specific criteria. The instruments used included a test on mathematical problem-solving abilities focused on derivative functions and a scale measuring mathematical resilience. Findings revealed a significant correlation of 0.819 between mathematical resilience and problem-solving abilities, while a correlation of 0.181 was attributed to other factors like conceptual understanding. Students with strong resilience and a solid grasp of concepts typically find it easier to tackle mathematical problems. Conversely, those with weaker resilience and limited understanding of the concepts struggle to comprehend the questions and develop effective strategies, leading to lower problem-solving capabilities. In conclusion, a notable relationship exists between mathematical resilience and students' ability to solve mathematical problems.